2013
DOI: 10.1111/tpj.12278
|View full text |Cite
|
Sign up to set email alerts
|

Imaging heterogeneity of membrane and storage lipids in transgenic Camelina sativa seeds with altered fatty acid profiles

Abstract: SUMMARYEngineering compositional changes in oilseeds is typically accomplished by introducing new enzymatic step (s) and/or by blocking or enhancing an existing enzymatic step(s) in a seed-specific manner. However, in practice, the amounts of lipid species that accumulate in seeds are often different from what one would predict from enzyme expression levels, and these incongruences may be rooted in an incomplete understanding of the regulation of seed lipid metabolism at the cellular/tissue level. Here we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 29 publications
6
66
0
Order By: Relevance
“…The metabolite heterogeneity including lipid compositions at the cellular level examined through MRI [288,289] and imaging mass spec [290][291][292][293] is visually striking [see figures and further description in [294]] and reminds us that plants operate at a systems level ( Fig. 1) with individual cells predisposed to differing metabolic objectives.…”
Section: Addressing the Challenges Of Multicellular Eukaryotic Metabomentioning
confidence: 93%
“…The metabolite heterogeneity including lipid compositions at the cellular level examined through MRI [288,289] and imaging mass spec [290][291][292][293] is visually striking [see figures and further description in [294]] and reminds us that plants operate at a systems level ( Fig. 1) with individual cells predisposed to differing metabolic objectives.…”
Section: Addressing the Challenges Of Multicellular Eukaryotic Metabomentioning
confidence: 93%
“…Such nonuniform distribution has been observed previously in cotton (Gossypium hirsutum; Horn et al, 2012) and Camelina spp. seeds (Horn et al, 2013); thus, this is not unique to maize but, apparently, is a more general phenomenon. However, the specifics of the distribution are unique for each species, likely owing to the different anatomy and biological properties of these seeds.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to seeds, TAG synthesis can also be accumulated in the flower petals, anthers, pollen grains, and leaves of a number of plant species (Kaup et al 2002;Kim et al 2002). However, the pathways of TAG synthesis appear to differ among plant species (Voelker and Kinney 2001;Troncoso-Ponce et al 2011) and plant tissues (Horn et al 2013), and their differences need to be further identified.…”
Section: Introductionmentioning
confidence: 98%